Effects of dietary inclusion of vitamin C on immune and antioxidant defence system in captive reared juvenile mahseer, Tor putitora (Hamilton, 1822) - Khan, Kifayat Ullah [UNESP]; Ullah, Imdad; Sarwar, Huda; Zuberi, Amina (Asian Fisheries Society, 2019)
The present trial was conducted to evaluate the effects of dietary L-ascorbyl-2-polyphosphate (vitamin C) on immune and antioxidant defence system in captive-reared juvenile mahseer (Tor putitora (Hamilton, 1822)). The experiment consisted of four treatments (3 replicates each), which received four semi-purified diets containing 0, 100, 200 and 300 mg.kg-1 of vitamin C. A total of 120 fish with an average initial body weight, 2.27 ± 0.01 g were distributed among 12 tanks (10 fish per tank). At the end of the 70-day experiment, all fish of each group were subjected to hypoxia stress for 48 h. Fish fed 300 mg.kg-1 vitamin C showed significantly increased (P < 0.05) serum lysozyme activity in response to hypoxia stress, followed by 200 and 100 mg.kg-1 vitamin C. Similar results were observed for glutathione peroxidase (GSH-Px), glutathione reductase (GSR) and superoxide dismutase (SOD) activity. After hypoxia, malondialdehyde (MDA) concentration was considerably reduced (P < 0.05) in fish fed 300 mg.kg-1 vitamin C. These results indicated that in stressful conditions feeding diets supplemented with 300 mg.kg-1 vitamin C would be better than 200 and 100 mg.kg-1 vitamin C, to obtain the optimum immune and antioxidant status of captive-reared juvenile mahseer.
Keywords: Fish nutritional physiology; Fish well-being; Immune-biochemical aspects; L-ascorbyl-2-polyphosphate